2020
DOI: 10.1002/we.2602
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the dynamic behaviour of 10 MW conventional and compact gearboxes for offshore wind turbines

Abstract: This study compares the dynamic behaviour of a conventional and a compact gearbox for the DTU 10 MW wind turbine supported on a monopile offshore structure. The conventional gearbox configuration is composed of two planetary epicyclic stages and one parallel stage, while the compact gearbox configuration consists of a fixed planetary stage and a differential compound epicyclic stage. The design methodology for these two gearboxes is described, and the final gearbox specifications show a lighter weight and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the basis of this work, future research should be conducted to further clarify the specific serviceability criteria and to establish connections between serviceability and safety criteria, also relating, for instance, to clearance requirements. One interesting work will be investigating the influence of floater design on nacelle surge acceleration and then on drivetrain safety of the 10-MW turbine based on the present work and authors' previous studies [17][18][19][20] in relation to drivetrain analysis.…”
Section: Serviceability Limitmentioning
confidence: 91%
“…On the basis of this work, future research should be conducted to further clarify the specific serviceability criteria and to establish connections between serviceability and safety criteria, also relating, for instance, to clearance requirements. One interesting work will be investigating the influence of floater design on nacelle surge acceleration and then on drivetrain safety of the 10-MW turbine based on the present work and authors' previous studies [17][18][19][20] in relation to drivetrain analysis.…”
Section: Serviceability Limitmentioning
confidence: 91%
“…Chen et al [20] presented a multi-source external environmental load modelling method and investigated resonance identification and dynamic responses under electromechanical coupling conditions. Wang et al [21] studied the dynamic characteristics of both conventional and compact wind turbine gearboxes, including load-sharing and fatigue damage assessment. Tan et al [22,23] performed a series of developments on an external environmental load acting on a gear transmission system of a wind turbine, revealing the effect of complex load conditions on the system, such as the voltage dip and platform motion and time-varying wind load.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the over-simplified model cannot accurately generate the coupling relationship and dynamic load among the independent components (Hu et al, 2017;He et al, 2021). In further research developments, detailed modeling of wind turbine dynamics models has gradually become the focus (Wang et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%